2012
DOI: 10.1186/1746-160x-8-32
|View full text |Cite
|
Sign up to set email alerts
|

Mini-implants in the palatal slope – a retrospective analysis of implant survival and tissue reaction

Abstract: BackgroundTo identify insertion procedure and force application related complications in Jet Screw (JS) type mini-implants when inserted in the palatal slope.MethodsSetting and Sample Population: The Department of Orthodontics, the University Hospital Münster. Forty-one consecutively started patients treated using mini-implants in the palatal slope. In this retrospective study, 66 JS were evaluated. Patient records were used to obtain data on the mode of utilization and complications. Standardized photographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…All studies reported side effects and complications associated with the use of orthodontic miniscrews. The studies, as summarized in Figure 2 , were identified as follows: 11 case reports, 13 - 23 8 retrospective longitudinal studies, 24 - 31 3 prospective controlled trials, 32 - 34 1 preliminary study, 35 and 1 case series. 36 All studies were conducted in a university setting and included both male and female participants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies reported side effects and complications associated with the use of orthodontic miniscrews. The studies, as summarized in Figure 2 , were identified as follows: 11 case reports, 13 - 23 8 retrospective longitudinal studies, 24 - 31 3 prospective controlled trials, 32 - 34 1 preliminary study, 35 and 1 case series. 36 All studies were conducted in a university setting and included both male and female participants.…”
Section: Resultsmentioning
confidence: 99%
“…All the miniscrews were surgically inserted according to the protocol suggested by the respective manufacturer. According to each orthodontic treatment plan, the miniscrews were positioned both in the maxilla and in the mandible, in the interradicular area, 13 , 15 , 18 , 19 , 21 - 24 , 32 , 33 , 36 palatal zone, 16 , 17 , 25 , 26 , 31 infrazygomatic crest, 28 , 36 ascending ramus, 26 or buccal shelf. 20 , 26 , 29 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations